Maintenance of balance between motor cortical excitation and inhibition after long-term training. (12th November 2016) - Dai, Wen; Pi, Yan-Ling; Ni, Zhen; Tan, Xiao-Ying; Zhang, Jian; Wu, Yin
Highlights: Motor cortical recruitment measured with the slope of motor-evoked potential input–output curve was increased in athletes. Motor cortical inhibition measured with short and long-interval intracortical inhibition was also increased in athletes. The balance between motor cortical excitation and inhibition is maintained during long-term training. Abstract: Motor learning with professional experience leads to cortical reorganization with plasticity. Long-term training facilitates motor cortical excitability. It is not clear how beneficial cortical plasticity is maintained during long-term training. We studied this question in 15 elite badminton athletes and 15 novices. We hypothesize that motor cortical excitation increases after long-term training and this is accompanied by increased motor cortical inhibition. Motor cortical excitation was measured with motor-evoked potential (MEP) input–output curve using transcranial magnetic stimulation (TMS). Motor cortical inhibition was measured with short-interval intracortical inhibition (SICI) and long-interval intracortical inhibition (LICI) by a paired-pulse TMS paradigm. We found MEP was increased at high TMS intensity and the MEP input–output curve was steeper in athletes compared to novices. Both SICI and LICI were also increased in athletes. In addition, both SICI and LICI were correlated with the slope of MEP input–output curve in athletes but not in novices. The slope of MEP input–output curve, SICI and LICI were also correlated with the training time in athletes. We conclude that both cortical excitation and cortical inhibition are increased, and that the balance between cortical excitation and inhibition is maintained during long-term training.